166k views
0 votes
Use the zero product property to find the solutions to the equation x2 - x - 6 = 0.

x= -3 or x = -2
x= -3 or x = 2
x=-2 or x = 3
x = 2 or x = 3

User Isanae
by
5.9k points

2 Answers

1 vote

Answer:

Yes, the right answer is C

Explanation:

User Mikheil Zhghenti
by
4.9k points
1 vote

Answer:

x=3 , x= -2

Explanation:

x^2 -x-6 =0

to solve to find the X's we need to factor.

to factor we need to find gcf.

since this problem has no coefficient in front of the x there is no GCF.

So we need to find the multiples of -6

What times What = -6

-3 and 2 = -6

we know x would need to be foiled to create x^2 so x will be in the parenthesis.

(x ) (x )

now we want to put the multiples into parenthesis

(x-3) (x+2)

but we need to set x-3 and x+2 = to 0

the 0 product property.

x-3=0

+3 +3

x=3

x+2=0

-2 -2

x=2

User THelper
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.